Manajemen Pendidikan Karakter di MINU Kraksaan Probolinggo untuk Mewujudkan Generasi Berakhlakul Karimah - Amalia, Nur Fitri (Universitas Pendidikan Indonesia Kampus Serang, 2022)
This research was conducted to know the management of character education at the Ibtidaiyah Madrasah to realize the generation of Akhlakul Karimah. The generation of Akhlakul Karimah is one of the major goals in the world of education, but the development of technologies that are increasingly advanced explosion with the morality of life increasingly extraordinary degradation. Critical morality is currently important for the alternative solution immediately. Management of character education is one of the effective ways to be implemented. This research method uses a qualitative descriptive approach. Data collection is done using interviews, observation, and documentation. Triangulation methods and source triangulation are carried out to ensure the validity of the data. Based on the results of the study found; 1) Management of character education can realize the morality of students MINU Kraksaan Probolinggo; 2) Excellent value and morality through the existence, coaching and integration; 3) Modeling morality values are carried out with examples of examples; 4) Develop a literacy value with 4C skills implementation; 5) Develop Islamic-based value education programs.